BIOLOGY TEACHERS’ TPACK IN THEIR INSTRUCTIONAL PLANNING FOR ONLINE-BASED PRACTICAL WORK - rifaatul muthmainnah (Indonesian Journal of Science and Education (IJOSE), 2021)
The transition from face-to-face to online practical work, in response to the Covid-19 pandemic, was unprecedented. Biology teachers are expected to integrate technology, pedagogy, and content knowledge to carry out online practical work successfully. Teachers' TPACK is performed, in part, during instructional planning. Therefore, study on how biology teacher performs their TPACK during online practical work is crucial. This study investigates biology teachers' TPACK on their instructional planning in practical work during online learning. The descriptive method was used with 42 participants who join as biology teacher association in Garut city. The Data was collected through a questionnaire, instructional planning document, and online interviews. The result shows several finding. First, biology teachers have a great belief on their TPACK. This indicates sustained integration of technology in learning even after this challenging time, for example, when blended learning is in the future. Second, biology teachers' TPACK based on their instructional planning is on three-level: recognizing, accepting, and adapting. Third, several opportunities, obstacles, and suggestions have been discussed by biology teachers. It is implied that this research promotes teacher professional development program to enhance their TPACK.